1992
DOI: 10.1152/ajpheart.1992.263.1.h1
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular recording and dye transfer in arterioles during blood flow control

Abstract: We tested for dye coupling between arteriolar smooth muscle cells (SMC) and endothelial cells (EC) and investigated the correspondence of vasomotor activity with changes in the membrane potential (Vm) of EC and SMC during blood flow control. Female golden hamsters (n = 8, 90-170 g) were anesthetized (pentobarbital sodium, 60 mg/kg ip). A cheek pouch was spread over an optical pedestal, transilluminated, and irrigated with physiological saline solution (37 degrees C, pH 7.4). Glass microelectrodes were filled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
111
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(116 citation statements)
references
References 0 publications
3
111
2
Order By: Relevance
“…1C) was <10 mV more negative than the vascular voltages measured at experimentally advantageous in vivo sites, such as the rat cremaster muscle (−42 mV) and the hamster cheek pouch (−46 mV) (27,28). Thus, a lack of internal pressurization does not account for the suprahyperpolarized membrane potentials of ∼-90 mV that we recorded in arterioles of nonperfused ex vivo <P30 ROP retinas (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…1C) was <10 mV more negative than the vascular voltages measured at experimentally advantageous in vivo sites, such as the rat cremaster muscle (−42 mV) and the hamster cheek pouch (−46 mV) (27,28). Thus, a lack of internal pressurization does not account for the suprahyperpolarized membrane potentials of ∼-90 mV that we recorded in arterioles of nonperfused ex vivo <P30 ROP retinas (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…Evidence supporting the role of gap junctions includes the observation that conducted vasomotor responses in hamster cheek pouch are abolished or attenuated with the application of putative gap junction uncouplers (35,43). Moreover, electron microscopy has demonstrated that neighboring endothelial and smooth muscle cells in renal vasculature (29), thoracic aorta (36), and iridial arterioles (18) are connected by gap junctions, which render these cells electrically and chemically coupled (2,3,18,40,34,23,28,42,43). See Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Because there is evidence that cAMP can enhance the molecular permeability and electrical conductance of gap junctions (14-18), we therefore investigated its ability to modulate dye transfer in the vessel wall. Attempts to demonstrate communication via myoendothelial gap junctions by injecting tracer dyes into individual endothelial cells are usually unsuccessful (25)(26)(27), presumably because of preferential diffusion of dye between cells in the endothelial monolayer, which are highly coupled by large gap junction plaques (19,28). To overcome this ''sink-source'' problem, we therefore selectively loaded the entire endothelium of femoral artery segments by intraluminal perfusion with the cell permeant dye calcein AM (29), so that fluorescence could be assessed in the media by confocal microscopy after hydrolysis to calcein.…”
Section: Discussionmentioning
confidence: 99%